Regular blood donation may help in the management of hypertension: an observational study on 292 blood donors. Issue 3 (8th December 2015) - Kamhieh‐Milz, Sundrela; Kamhieh‐Milz, Julian; Tauchmann, Yvonne; Ostermann, Thomas; Shah, Yatin; Kalus, Ulrich; Salama, Abdulgabar; Michalsen, Andreas
Abstract : BACKGROUND: Hypertension is one of the leading global risks for cardiovascular events worldwide. There is preliminary evidence that regular blood donation may be beneficial. STUDY DESIGN AND METHODS: Unselected blood donors were included in this observational study. Blood pressure (BP) was measured before and after blood donation, with participants donating between one and four occasions in a 1‐year study period. RESULTS: In this study, 292 donors were enrolled. At baseline, 146 had elevated BP (>140/90 mmHg). In hypertensives, after four blood donations, systolic and diastolic blood pressure (SBP and DBP, respectively) decreased from a mean of 155.9 ± 13.0 to 143.7 ± 15.0 mmHg and from 91.4 ± 9.2 to 84.5 ± 9.3 mmHg, respectively (each p < 0.001). There was a clear dose effect with decreasing BP by the increasing number of blood donations. After at least four blood donations, donors with Stage II hypertensive baseline values (≥160 mmHg SBP and/or ≥100 mmHg DBP) were found to have the most marked reduction in BP, with 17.1 mmHg (95% confidence interval [CI], −23.2 to −11.0; p < 0.0001) and 11.7 mmHg (95% CI, −17.1 to −6.1; p = 0.0006) for SBP and DBP, respectively. The decrease in BP was not significantly associated with changes of blood count or variables of iron metabolism. CONCLUSIONS: Regular blood donation is associated with pronounced decreases of BP in hypertensives. This beneficial effect of blood donation may open a new door regarding community health care and cost reduction in the treatment of hypertension.